Optimization of Cash Waqf-Based Crowdfunding: An Alternative Finance for Quality Education - Lahuri, Setiawan Bin; Lutfiah, Asti (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Education in Indonesia still has significant problems such as the lack of adequate learning facilities, the low quality of education, the high cost of education and the large number of students who drop out of school. The main problem of Indonesian education is the high cost of education, making it difficult for students with middle to lower economy to continue their education. Waqf as an Islamic philanthropy can be a solution to education financing, supported by the MUI Fatwa with the provision of waqf developed with sharia securities through crowdfunding platforms. The regulation of cash waqf through the MUI (Indonesian Ulema Council) Fatwa was developed following the times in Fatwa No. 140/DSN-MUI/VIII/2021 which explains waqf as one of the sharia securities as financing waqf. However, the collection of waqf funds for education financing is still not optimal. So, this research aims to provide an alternative to waqf as an Islamic social financing system that can develop the quality of education in Indonesia with the aim of SDGs (Sustainable Development Goals) in creating quality education. This research method uses library research method with literature study analysis through MUI fatwa approach. The results of this study explain the contract scheme that can make it easier for waqif to waqf through crowdfunding in the form of education financing investment, namely the wakalah bil istismar contract and the syirkah contract. However, crowdfunding for education financing is not widely applied for.